Statement on recent disturbances - TUC, 1958 (1958)
1958 1945-1960 "Statement on recent disturbances - TUC, 1958" [T0364.jpg], 1958, Trades Union Congress This statement was circulated to delegates attending the 1958 TUC Congress in Bournemouth. It condemns the riots and racist attacks which had taken place in Nottingham and Notting Hill Gate, London.